2007
DOI: 10.1128/jcm.02012-06
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Clinically RelevantExophialaSpecies in the United States

Abstract: Numerous members of the genus Exophiala are potential agents of human and animal mycoses. The majority of these infections are cutaneous and superficial, but also fatal systemic infections are known. We re-identified 188 clinical isolates from the United States, which had a preliminary morphological identification of Exophiala species, by sequencing internal transcribed spacer (ITS) region of the rRNA. Molecular identifications of the strains were as follows, in order of frequency: 55 E. dermatitidis (29.3%), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
252
0
17

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(279 citation statements)
references
References 34 publications
10
252
0
17
Order By: Relevance
“…For molecular species identification, percent identities of just the ITS locus were considered, because it offers a higher resolution than the relatively conserved LSU gene (Iwen et al 2002). If the identity of the ITS sequence of a studied strain to its closest match was ≥99 %, they were considered conspecific (Zeng et al 2007). In rare cases where more than one species yielded 99 % identity, but none of them reached 100 %, the studied strain was identified only to genus level.…”
Section: Dna Sequence Analysesmentioning
confidence: 99%
“…For molecular species identification, percent identities of just the ITS locus were considered, because it offers a higher resolution than the relatively conserved LSU gene (Iwen et al 2002). If the identity of the ITS sequence of a studied strain to its closest match was ≥99 %, they were considered conspecific (Zeng et al 2007). In rare cases where more than one species yielded 99 % identity, but none of them reached 100 %, the studied strain was identified only to genus level.…”
Section: Dna Sequence Analysesmentioning
confidence: 99%
“…Around 30 different species of this genus have been isolated from different environmental sources of tropical and subtropical regions [2]. These fungi are known to cause systemic as well as subcutaneous cystic lesions [3]. The genus Exophiala found in the environment is known to cause subcutaneous cystic infection in immunocompetent as well as the immunosuppressed individual [4].…”
Section: Discussionmentioning
confidence: 99%
“…E. jeanselmei is the most frequently cited of the Exophiala species as a human pathogen, however sequence data has subsequently shown that E. jeanselmei is a species complex and that many of these case reports would represent other species if characterized at the molecular level. The most common clinically relevant species in the United States is E. dermatitidis (Zeng et al, 2007). Other species such as E. moniliae, E. oligosperma and E. spinifera have been implicated as well (Zeng et al, 2007).…”
Section: Mycologymentioning
confidence: 99%